(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The works of the modern dramatist consist of reduced forms of drama that depict declining human capacities. The primary focus of their works revolved around the revelation of the essence of consciousness and the quest for self-identity in its entirety. They conduct extensive research on the purpose of life. Their thoughts and issues are addressed through their own experiences and integrated into the framework of their work. The human condition and life are tragically portrayed in their plays. Drama evolves with a progressing civilization and emerges as a potent influence in human affairs, challenging established customs and social systems that perpetuate exploitation and humiliation. It has evolved to portray a bleak and unvarnished portrayal of the world, filled with harsh truths, human anguish, terror, and loneliness, rather than providing only amusement. The contemporary writers portrayed home relationships and societal issues that were universally recognized by the audience in their dramas.